Noncoupled NADH:Ubiquinone Oxidoreductase of Azotobacter vinelandii Is Required for Diazotrophic Growth at High Oxygen Concentrations - Bertsova, Yulia V. (American Society for Microbiology, 2001)
The gene encoding the noncoupled NADH:ubiquinone oxidoreductase (NDH II) from Azotobacter vinelandii was cloned, sequenced, and used to construct an NDH II-deficient mutant strain. Compared to the wild type, this strain showed a marked decrease in respiratory activity. It was unable to grow diazotrophically at high aeration, while it was fully capable of growth at low aeration or in the presence of NH(4)(+). This result suggests that the role of NDH II is as a vital component of the respiratory protection mechanism of the nitrogenase complex in A. vinelandii. It was also found that the oxidation of NADPH in the A. vinelandii respiratory chain is catalyzed solely by NDH II.